(untitled) (Advancements in Homeopathic Research, 2022)
One of the major occupational risks for people working in the construction or cement industries is allergic contact dermatitis, which frequently affects the workers’ quality of life and results in significant financial loss. The hands of cement workers come into touch with cement on a frequent basis, making them susceptible to developing hand contact dermatitis again and making a full recovery exceedingly challenging. The contact dermatitis in homoeopathy has been the subject of numerous prior researches. This case study demonstrated the effectiveness of the homoeopathic drug Graphites 30C on allergic contact dermatitis, with slow improvement at first and full recovery at the end.